Combined clerking – streamlining emergency admissions. (2019) - Gilbert, Holly; Reynish, Dominic; Richter, Dan; Neville, Ian; Thavanesan, Kamy; Sopher, Mark; Martin, David; Willington, Robert; Byrom, Richard; Ghafoor, Imran; O'Donnell, Alyson
No abstract available